Building alliances and consensus around social-ecological rewilding in Chile - Root-Bernstein, Meredith; Guerrero-Gatica, Matías (Frontiers in Conservation Science, 2024)
We provide a case study of how we position our rewilding project in central Chile in order to find scientific and social support and build alliances, collaborations, and consensus. Our core vision focuses on reintroducing guanacos (Lama guanicoe) to central Chile in order to provide natural restoration and ecosystem processes in espinal woodlands dominated by the native tree Vachellia [Acacia] caven. We envision a scenario of "socio-ecological rewilding" with widespread guanaco browsing in woodlands and guanaco migration across the region, coexisting with multiple human uses of the landscape. Guanacos would ideally be managed by regional collectives who could benefit from guanaco tourism, sustainable harvest of their fiber (wool), and regulated hunting. Our wider vision for reintroductions and integrated conservation management extends to a set of other species that may have coexisted with guanacos and V. caven at various points in the past, but more research is necessary to establish and gain support for evidence-based baselines. Our strategy is to inspire actors with greater resources (land, money, influence) to share our vision and implement it, in collaboration with the NGO that we have formed to support our projects. Over ten years, circulating alternate interpretations and a novel imaginary of how central Chile was in the past and could be in the future, along with developing and testing scientific hypotheses, has moved our vision from an idea shared by two people to one that a wide variety of actors publicly embrace.